PEMANFAATAN MEDIA INTERAKTIF PhET UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR PADA MATA PELAJARAN IPA - Rahmiati, Devi; Pusparani, Herlina (Universitas Negeri Medan, 2023)
Science learning materials in class such as electricity and alternative energy sources that cannot be presented directly to class requires the right media. This study aims to determine whether PhET interactive media is effective in improving the learning outcomes of class VI students in science subjects. This type of research is classroom action research conducted in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. Each cycle consists of two meetings. The subjects of this study were 27 students in class VI A at Guntur Elementary School, Cirebon City. The results showed that PhET is an interactive medium that is easy to use and makes it easy for students to understand the material on electrical circuits and alternative energy sources. Through PhET, students simulate electric circuits and convert alternative energy sources into electricity. Students are more active and enthusiastic when learning. The learning outcomes of all students can increase because PhET is a suitable medium for learning science because the media is very interesting and interactive so students understand the material more easily and their learning outcomes increase.